Delayed surgical closure (secondary intention) using the Figueiredo technique: a case series study - Larissa Helena Marques Carrai; Evelyn Freitas Rodrigues; Thais Feres Moreira Lima; Maria da Glória Martin Sasseron; Antonio Gomes-Neto (Sociedade Brasileira de Dermatologia (SBD), 2023)
Surgical wounds, when not amenable to primary healing, can be treated using surgical flaps or grafts, increasing surgery complexity and costs. Seeking to facilitate and optimize access to surgical treatment of malignant neoplasms of the skin, the dressing using the Figueiredo technique is a good therapeutic option due to its easy execution and reproducibility, low cost, and effectiveness. We report a series of cases using this technique after the excision of non-melanoma skin tumors in the extremities.